Observatorio turístico como herramienta de gestión y desarrollo del turismo sostenible en la zona norte de Manabí - Torres Apolo, Daily Alejandra (2022)
The present work had as objective the elaboration of a proposal for a Tourist Observatory as a tool for the management and development of sustainable tourism in the northern area in Manabí. The research has a mixed exploratory and descriptive approach and comprises three stages. The first stage consisted of a sectoral analysis of tourism. Probabilistic and non-probabilistic sampling surveys were applied, the first focused on the study of the potential tourist demand and the second directed at the tourist actors in order to know their perception about the management, use and information needs, whose results contributed to the comprehensive analysis of the study area to establish the conditions on which a tourist observatory would be implemented. In the second stage, a comparative analysis of various international observatories that supported the proposal of the observatory in question was carried out. Its organizational structure was raised, as well as the operational processes and the respective budgets for its implementation. Using the Delphi method, the experts were selected to analyze the indicators and select them, taking into account management, economic, social and environmental impact aspects. The policies for the dissemination and management of the information produced were determined and a strategic communication plan was proposed for the observatory that would allow a correct management of its outputs in the short and long term. The investigation showed that the northern area of the province of Manabí has the conditions and needs required for the implementation of a sustainable tourism observatory